Promessa é dívida: Efeitos da inconsistência de informantes na confiança seletiva de crianças pré-escolares - Melnicky, Laura Cunha (Universidade Federal de São Carlos, 2022)
Recent studies investigated the development of selective trust or the ability to discriminate good and bad informants in new learning situations. One question, however, remains little explored: can these judgements be also influenced by a history of broken promises and by the reasons that led to the promises being broken? The goal of the present study was to search for an answer to this question. A second goal was to test a possible correlation between selective trust and theory of mind. Forty-eight children were recruited, and four of them participated in a pilot study. Data analysis was conducted, therefore, with 44 children aged 5 (Mage= 5 yrs e 10 mos, DP = 3,7 mos) e 6 anos (Mage= 6 yrs e 8 mos, DP = 3.5 mos). Children were assessed by a selective trust task and the Morally Relevant Theory of Mind task (MoToM). Participants were randomly distributed into three conditions that differ in relation to the situation presented in the selective trust task. In the first condition (C1), one of the characters always promised something to a friend but broke the promise without a plausible motive; a second character likewise did not keep his promises, but he had plausible reasons for doing so. In the second condition (C2), one character made promises and fulfilled them; and another character did not keep his promises but had plausible reasons for breaking them. In a third condition (C3), a character who fulfilled promises is contrasted with a character who broke his promises without a plausible explanation. During a test phase, children were asked to choose one of the characters as a source of information in new learning situations. No gender or age effects were found. Data analysis showed that participants’ performance in the selective trust task was not different from chance. Additionally, no signicant differences were found between the three conditions. No clear preference for the character who fulfills his promises was found and neither for the one who breaks promises for justifiable reasons. Future studies should test this procedure with older children as well as use tests in different domains, not only the game situation used in the present work.
Promise is debt: Effects of informant inconsistency on selective trust of preschool children
Keywords: Confiança seletiva; Promessas; Teoria da mente; Crianças; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::PROCESSOS PERCEPTUAIS E COGNITIVOS; DESENVOLVIMENTO